ERROR ANALYSIS ON THE USE OF PREPOSITIONS IN THE STUDENTS’ WRITING COMPOSITION - Nurul Izah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This research was conducted to describe the kinds of preposition errors found in the students’ writing composition, to discover the kind of preposition errors mostly produced by the students, and to find out the sources of the errors. This study applied a descriptive qualitative research design. The researcher observed the 50 students’ descriptive text from two classes who were chosen using purposive sampling. The instruments used were the researcher herself as the main instrument and some tables from Utari (2017) to collect, to analyze, to classify, and to interpret the data. The data showed that there were 74 items where the errors of omission were 15 items or 20.2%, errors of addition were 14 items or 18.9%, errors of misformation were 44 items or 59.4%, and error of misordering was 1 item or 1.3%. Moreover, the preposition errors made by the students were caused by interlingual errors with 42 items, and intralingual errors with 32 items. Therefore, the preposition errors mostly produced by the students were errors of misformation which were mostly caused by their first language interference. The researcher could say that the students were lack of preposition mastery, so it made them applying their own rules for expressing their idea. The suggestions for the next researchers are to work more on the solutions of the sources of the errors made by the students and to analyze the other object besides students’ text, for example on the students’ video project. Keywords: Error, Error Analysis, Preposition, and Descriptive Text